Antimicrobial Drug-Induced Thrombocytopenia: A Review of the Literature - Loo, Angela S.; Gerzenshtein, Lana; Ison, Michael G. (Seminars in Thrombosis and Hemostasis, 2012)
The incidence of drug-induced thrombocytopenia (DIT) is not well-defined, but is estimated to occur at a minimum of 10 cases per million per year. This review will focus on the potential DIT associated with specific antibacterial, antifungal, antiviral, and antiparasitic agents. Case reports, cohort studies, and clinical trials were identified using PubMed search terms for each antimicrobial along with the Boolean combiner AND to match with the following outcomes: thrombocytopenia and bleed. Thrombocytopenia was defined as a platelet count of < 100 × 109/L or a decrease in platelet count of at least 50% from baseline. A majority of the data supporting antimicrobial-induced thrombocytopenia consist of case reports and small studies. However, clinicians should be vigilant in monitoring patient platelet counts, as an immune-mediated mechanism is frequently responsible for this hematologic adverse effect and is therefore unpredictable.
Keywords: antimicrobials; thrombocytopenia; coagulopathy